Efeito do treinamento físico domiciliar associado ao uso de tecnologia em pacientes com doença renal crônica terminal - Pillatt, Ana Paula (2013)
The aim of this study was to evaluate the effect of a domiciliary physical training associated with the use of technology in patients with kidney failure chronic. It is a controlled clinical trial, composed of 32 patients who were randomized to the control group (G1) and intervention group (G2). Anthropometric measurements were evaluated by body mass index and waist circumference, functional capacity with Sit and Stand Test, flexibility by 3rd finger-solo Test, the quality of life through the questionnaire KDQOL-SF, the activities of daily life with the Katz and Lawton scales and renal function by clinical examination. The G1 did not do any kind of intervention. The G2 was instructed to perform a training session of muscular resistance exercises at home, four times a week, for three months, with the aid of video lessons recorded on three DVDs. After three months, both groups repeated the evaluations. For data analysis, it were used the Kolmogorov-Smirnov test, Mann-Whitney test and the Pearson chi-square. The groups proved to be homogeneous (p>0,05) either at the baseline as much as in the follow-up evaluation, performed at the end of the third month. The home physical training associated to the use of technology has not proved effective for patients with kidney failure chronic